The Influence of Occupational Safety and Health and the Application of Transactional Leadership on Employee Performance Through Work Discipline at PT Wira Duta Fiberglass - Robert Sanjaya Sembiring; Prihatin Lumbanraja; Yeni Absah (Indonesian Journal of Business Analytics, 2025)
The manufacturing industry often involves work with a high risk of work accidents and employees tend to be followers or workers who only follow the direction of the leadership and standard operating procedures from the company. This study aims to analyse the effect of occupational safety and health and the application of transactional leadership on employee performance through work discipline at PT Wira Duta Fiberglass. This study reveals that the factor that has the most positive and significant effect on employee performance is occupational safety and health, and the factor that has the most positive and significant effect on work discipline is transactional leadership, transactional leadership has a positive and significant effect on employee performance, occupational safety and health has a positive and insignificant effect on work discipline, work discipline has a positive and significant effect on employee performance, occupational safety and health has a positive and insignificant effect on employee performance through work discipline, and transactional leadership has a positive and significant effect on employee performance through work discipline.